Assessing land degradation dynamics in the Buyuk Menderes River Basin: a comprehensive spatial modelling approach - Kulahlioglu, Muge; Akin, Anil; Berberoglu, Suha; Sahingoz, Merve; Cilek, Ahmet; Donmez, Cenk (Springer, 2025)
Land degradation stands as a pivotal determinant for the viability of sustainable ecosystems, with its impact on biodiversity closely intertwined with the intricate interplay of natural, physical, and cultural elements within landscapes. This study evaluates land degradation (LD) within the Buyuk Menderes River Basin by employing a comprehensive suite of indicators, which have been simulated using advanced spatial modelling techniques. Specifically, indicators such as Net Primary Production (NPP), erosion and Soil Organic Carbon (SOC) have been rigorously analysed to delineate the evolving landscape dynamics. Areas affected by LD in Buyuk Menderes were identified using time-series analysis of several vegetation index data derived from satellites, climate data between 1975 and 2018 together with other environmental gradients including, soil, geomorphology, vegetation and water. NASA-CASA, PESERA and Random forest approaches were adopted for NPP, erosion and SOC modelling respectively. Modelling accuracies for each approach were acquired as 83%, 85.5% and 65%. Modelling outcomes than integrated to determine degraded lands within the landscape units, and degradation levels were presented in percentiles for each land/use land cover class. The results showed that more than 50% of the river basin faces to degradation threat due to water problems related to climate change. By incorporating such comprehensive datasets, our study aims to provide valuable insights into land degradation processes and facilitate informed decision-making for sustainable landscape planning practices.
Keywords: Land degradation; Geospatial modelling; River Basin; Sustainable environment management